Innovative Learning Strategies (Differentiated Learning Perspective on Merdeka Curriculum) - Safrudin, Safrudin; Wijaya, Erwin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Innovative learning strategies are essential approaches in addressing global challenges and rapid technological developments in the era of the Merdeka Curriculum. From the perspective of differentiated learning, this approach views each learner as a unique individual with different needs, interests, and learning styles. This article discusses innovative learning strategies that can be applied in the context of the Merdeka Curriculum, with a focus on differentiated learning. Firstly, emphasis is placed on the use of technology as a learning tool. Utilizing online platforms, educational applications, and learning software can facilitate differentiation in presenting materials and adjusting the level of difficulty according to each student's abilities. Secondly, project-based approaches are integrated into learning to stimulate creativity and problem-solving. These projects can be tailored to the interests and talents of students, creating meaningful learning experiences. Furthermore, cooperative and collaborative learning strategies are implemented to enhance social interaction and student engagement. Through group cooperation, learners can support and understand each other's differences. The importance of formative assessment is also highlighted in this article. By providing regular feedback, teachers can understand the development of each student and devise appropriate differentiation strategies. In implementing these innovative learning strategies, the role of the teacher as a facilitator is crucial. Teachers need to have the skills to identify the individual needs of students, design challenging activities, and provide appropriate support. This article contributes to an understanding of how innovative learning in the perspective of differentiated learning can be integrated into the Merdeka Curriculum. By adopting these strategies, it is expected to create an inclusive, supportive, and stimulating learning environment that fosters the development of each student's potential.